Cloud Computing Technology - Huawei Technologies Co., Ltd (Springer Nature Singapore : Imprint: Springer, 2023)
This open access book introduces cloud computing and related technologies from the concept, technology, and architecture of cloud computing, combined with typical application cases of cloud; provides students with a more complete knowledge framework in the field of cloud computing; and lays the foundation for future research, development, and further study in cloud computing, big data, and other related fields. As the world's leading provider of ICT (information and communication technology) infrastructure and intelligence terminals, Huawei's products are already available in a number of areas, including connectivity, security, wireless, storage, cloud computing, intelligent computing, and artificial intelligence.